Utopia - More, Thomas, Saint, 1478-1535 (Yale University Press, 2014)
"Saint Thomas More's Utopia is one of the most important works of European humanism and serves as a key text in survey courses on Western intellectual history, the Renaissance, political theory, and many other subjects. Preeminent More scholar Clarence H. Miller does justice to the full range of More's rhetoric in this masterful translation. In a new afterword to this edition, Jerry Harp contextualizes More's life and Utopia within the wider frames of European humanism and the Renaissance."--Page 4 of cover
Previous edition of this translation: New Haven, Conn.; London: Yale Nota Bene, 2001.
Keywords: Utopias -- Early works to 1800.; Utopies -- Ouvrages avant 1800.; POLITICAL SCIENCE -- Political Ideologies -- Communism & Socialism.; PHILOSOPHY -- History & Surveys -- Renaissance.; Utopias; Early works